DIFFERENCES BETWEEN CORELDRAW AND ADOBE ILLUSTRATOR SOFTWARE - Khakimov son of Bakhtiyor Muzaffar (Galaxy International Interdisciplinary Research Journal, 2024)
Discusses the differences between the two most popular programs for creating designs - vector graphics programs. The difference between CorelDraw and Adobe Illustrator CC software is that each has its own features. The advantages of CorelDraw and Adobe Illustrator programs are analyzed and the opinions obtained are presented.